Nitrogen and boron nutrition in grafted watermelon I: Impact on pomological attributes, yield and fruit quality. - Kemal Yalçın Gülüt (Public Library of Science (PLoS), 2021)
Watermelon is extensively consumed fruit across the globe. However, limited is known about interactive effect of nitrogen (N) and boron (B) nutrition on pomological, yield and fruit quality attributes of grafted watermelon. This two-year study tested the influence of different N and B doses on pomological, yield and fruit quality attributes of grafted watermelon under field conditions in Çukurova plains of Turkey. Four different N (0, 90, 180 and 270 kg ha-1) and two B doses (0 and 2 kg ha-1 B) were tested. The individual and interactive effects of N and B significantly altered pomological, yield and fruit quality attributes during both years. Overall, application of 270 kg ha-1 N and 2 kg ha-1 B improved yield, pomological and fruit quality attributes during both years. The highest values for yield, main stem length, stem diameter, fruit weight, fruit width, number nodes and branches per stem were recorded for 270 kg ha-1 N during both years. However, rind thickness was not altered by N application. Similarly, the highest values for quality attributes such as sucrose, glucose, fructose, citric acid, tartaric acid and ascorbic acid were noted for 270 kg ha-1 N during both years. Interestingly, no N application and 90 kg ha-1 N recorded the highest values of maleic acid during both years. The highest values of rind thickness, fruit length, fruit width and fruit weight were noted for 2 kg ha-1 B during both years, while B application had no effect on main stem length, main stem diameter, number of nodes and number of branches. Regarding N by B interactions, 180 and 270 kg ha-1 N with both B doses observed the highest values for yield, pomological and quality attributes during each year. These results indicate that N has significant contribution towards yield, pomological attributes and fruit quality of grafted watermelon. Therefore, N should be applied at the rate of 270 kg ha-1 for better yield, pomological attributes and fruit quality. Nonetheless, where necessary grafted watermelon should be fertilized with 2 kg ha-1 B for better fruit quality and pomological attributes.